Understanding the Drivers of Public School Performance and Efficiency in the Philippines - World Bank Group (World Bank, Washington, DC, 2016)
This note attempts to identify the factors associated with differences in overall school performance and efficiency. It draws on data from the Philippines Public Education Expenditure Tracking and Quantitative Service Delivery Study (PETS-QSDS), which tracked public education spending and assessed the quality of the systems governing the use of these funds. The note also draws on the findings from other policy notes in this series to identify the key factors that determine the links between public spending and education outcomes. The note found that school performance is related to several of these key factors including school governance and school infrastructure. It also found that student and school characteristics, school-level accountability mechanisms, and some teacher characteristics are associated with how efficiently schools can convert their financial, physical, and human resources into improved education outcomes. However, given the limitations of using cross-sectional data, the findings are not strong, and factors associated with good performance tend to vary a lot according to the level of education and the performance measures that were being analyzed. While more rigorous research is needed, the policy note provides tentative evidence that the factors often associated with better performance are not functioning effectively in the Philippines.